Impact of the Covid-19 Pandemic on Children Continues: What Can We Do to Help?. Issue 3 (May 2021) - Beal, Judy A.
Abstract : The COVID-19 pandemic has had a profound impact on children and families. Our pediatric nursing expert, Dr. Beal, reviews recent guidance from the American Academy of Pediatrics and a state health agency to offer suggestions for resources for pediatric nurses so they can better help their patients and families.